2016
DOI: 10.4236/me.2016.75070
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and Mobility: Gatsby in the Americas

Abstract: We present evidence that the recent fall Latin America inequality has been associated with higher social mobility across countries and over time. This correlation refers to what Alan Krueger and his CEA staff labeled the Great Gatsby Curve, but this is one of the first papers to test the Gatsby correlation over time. Our search for Gatsby curve correlates starts with classic mobility models where high Mincer coefficients and skilled wage-premia enhance wealthier parents' ability to impart advantage to their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Jerrim and Macmillan (2015) used data from twenty-three countries that are members of the Organization for Economic Cooperation and Development (OECD) and concluded that educa-tion is the main channel in the relationship between intergenerational mobility and inequality. Brahim and McLeod (2016) corroborated the existence of the curve for Latin American countries. The authors asserted that the explanation of the decreasing tendency of inequality in most countries can be found in the improvement of the population's living conditions and the raise of social mobility among generations.…”
Section: Literature Reviewsupporting
confidence: 60%
“…Jerrim and Macmillan (2015) used data from twenty-three countries that are members of the Organization for Economic Cooperation and Development (OECD) and concluded that educa-tion is the main channel in the relationship between intergenerational mobility and inequality. Brahim and McLeod (2016) corroborated the existence of the curve for Latin American countries. The authors asserted that the explanation of the decreasing tendency of inequality in most countries can be found in the improvement of the population's living conditions and the raise of social mobility among generations.…”
Section: Literature Reviewsupporting
confidence: 60%
“…It has been mentioned by Nobel Prize winners (see, e.g., Heckman, 2013) and has been extensively addressed by the mainstream press (see, e.g., The Economist, 2013; The Guardian, 2012) and high‐ranking policymakers (see, e.g., House, 2013; Obama, 2013). The GGC has also been addressed in a long list of recent publications in peer‐reviewed journals (see, e.g., Boudreaux, 2014; Brahim & McLeod, 2016; Chetty et al, 2014; Corak, 2013; Güell et al, 2018; Jerrim & Macmillan, 2015; Lefgren et al, 2015; Neidhöfer, 2019).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%